Australasian ants of the subfamily Heteroponerinae (Hymenoptera: Formicidae): (2) the species-group of Heteroponera relicta (Wheeler),with descriptions of nine new species and observations on morphology, biogeography and phylogeny of the genus - Taylor, Robert W. (Zootaxa, 2015)
Workers and available gynes of Heteroponera relicta and nine new related morphospecies from northeast Queensland tropical rainforest are described in two species complexes: H. relicta (Wheeler), H. darlingtonorum, H. lioprocta, H. monteithi, H. rhodopygea, H. viviennae and H. wilsoni spp. n. (Heteroponera relicta complex); H. ecarinata, H. pendergrasti and H. trachypyx spp. n. (Heteroponera ecarinata complex). Known gynes (of 3 relicta-complex species) are flightless physogastric ergatoids. Biogeography and evolution of the group and of Heteroponera at large are reviewed.